Development of a novel fusion imaging technique in the diagnosis of hepatobiliary‐pancreatic lesions. Issue 3 (10th January 2013) - Soga, Koichi; Ochiai, Jun; Kassai, Kyoichi; Miyajima, Takashi; Itani, Kenji; Yagi, Nobuaki; Naito, Yuji
Abstract Introduction Multi‐row detector computed tomography (MDCT) and magnetic resonance cholangiopancreatography (MRCP) play an important role in the imaging diagnosis of hepatobiliary‐pancreatic lesions. Here we investigated whether unifying the MDCT and MRCP images onto the same screen using fusion imaging could overcome the limitations of each technique, while still maintaining their benefits. Moreover, because reports of fusion imaging using MDCT and MRCP are rare, we assessed the benefits and limitations of this method for its potential application in a clinical setting. Methods The patient group included 9 men and 11 women. Among the 20 patients, the final diagnoses were as follows: 10 intraductal papillary mucinous neoplasms, 5 biliary system carcinomas, 1 pancreatic adenocarcinoma and 5 non‐neoplastic lesions. After transmitting the Digital Imaging and Communication in Medicine data of the MDCT and MRCP images to a workstation, we performed a 3‐D organisation of both sets of images using volume rendering for the image fusion. Results Fusion imaging enabled clear identification of the spatial relationship between a hepatobiliary‐pancreatic lesion and the solid viscera and/or vessels. Further, this method facilitated the determination of the relationship between the anatomical position of the lesion and its surroundings more easily than either MDCT or MRCP alone. Conclusion Fusion imaging is an easy technique to perform and may be a useful tool for planning treatment strategies and for examining pathological changes in hepatobiliary‐pancreatic lesions. Additionally, the ease of obtaining the 3‐D images suggests the possibility of using these images to plan intervention strategies.